A Proposed Hypothesis on Dementia: Inflammation, Small Vessel Disease, and Hypoperfusion Is the Sequence That Links All Harmful Lifestyles to Cognitive Impairment - Hakim, Antoine M. (Frontiers in Aging Neuroscience, 2021)
There is growing consensus that certain lifestyles can contribute to cognitive impairment and dementia, but the physiological steps that link a harmful lifestyle to its negative impact are not always evident. It is also unclear whether all lifestyles that contribute to dementia do so through the same intermediary steps. This article will focus on three lifestyles known to be risk factors for dementia, namely obesity, sedentary behavior, and insufficient sleep, and offer a unifying hypothesis proposing that lifestyles that negatively impact cognition do so through the same sequence of events: inflammation, small vessel disease, decline in cerebral perfusion, and brain atrophy. The hypothesis will then be tested in a recently identified risk factor for dementia, namely hearing deficit. If further studies confirm this sequence of events leading to dementia, a significant change in our approach to this debilitating and costly condition may be necessary, possible, and beneficial.